BERITA BOHONG DAN MENYESATKAN TENTANG INFORMASI PRODUK DALAM KONTRAK ELEKTRONIK - Sudjana, Sudjana (Res Nullius Law Journal, 2022)
Freedom of expression through the use of Information Technology is carried out by taking into account the restriction not to contain false and misleading news. This study aims to determine the legal consequences of false and misleading news regarding product information in electronic contracts and to formulate the legal liability of business actors against false and misleading news about product information in electronic contracts. Typology The research methods are normative research, legal approach, data collection techniques through document studies and qualitative data analysis methods. The results of the study show that false news related to product information in electronic contracts violates subjective conditions, resulting in the agreement being cancelled, while "misleading" includes objective requirements because the non-fulfillment of the halal conditions causes the agreement to be null and void. lying and misleading regarding product information in electronic contracts based on the principle of strict liability and the form of liability is the imposition of contractual sanctions in civil law, product liability, administrative liability and criminal liability. Suggestion: Business actors must have good faith in making contracts and the Electronic Information and Transaction Law needs to regulate liability as a result of providing electronic information that contains false and misleading news.